Adhesive tape for electronic component processing and method for manufacturing electronic component
Patent Information
- Application Number
- JP2023141182
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-03-13
AI Technical Summary
【0014】 本開示は、基材のエキスパンド性が良好であり、ウォータージェットレーザー加工時およびエキスパンド時の基材の破断を抑制できる電子部品加工用粘着テープを提供できる。
Smart Images

Figure 2025034667000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an adhesive tape for processing electronic components and a method for manufacturing electronic components. [Background technology]
[0002] In a so-called dicing process in which a substrate to be processed is divided into chips, an adhesive tape called a dicing tape is used to protect and fix the substrate to be processed and the chips.
[0003] In recent years, a dicing method using a laser guided by a water jet has been proposed. This method is hereinafter referred to as water jet laser processing.
[0004] Adhesive tapes usually have a substrate and an adhesive layer. Generally, resin films are used as substrates of adhesive tapes. On the other hand, as described in Patent Documents 1 to 4, for example, in the case of water jet laser processing, in order to suppress chipping caused by splashing of water, porous substrates such as nonwoven fabrics, woven fabrics, knitted fabrics, and perforated sheets that can transmit water flow are used as substrates of adhesive tapes. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 3824874 [Patent Document 2] Patent No. 4087144 [Patent Document 3] Patent No. 5000370 [Patent Document 4] JP 2005-167042 A [Patent Document 5] Patent No. 4886937 Summary of the Invention [Problem to be solved by the invention]
[0006] In the method for manufacturing electronic components, the dicing step is followed by an expanding step in which the adhesive tape is stretched to increase the spacing between the chips, and a pick-up step in which the chips are picked up from the adhesive tape.
[0007] However, when a porous substrate is used as the substrate for an adhesive tape, there is a problem that since many porous substrates generally have poor expandability, the distance between chips cannot be sufficiently increased, making it difficult to pick up the chips.
[0008] In addition, some laser beams are easily absorbed by water, while others are not. Therefore, in water jet laser processing, the use of short-wavelength laser beams is being considered in order to reduce the absorption rate in water and increase processing efficiency.
[0009] However, in general, the shorter the wavelength of the laser light, the higher the energy and the higher the absorption rate for the material. Therefore, when a short-wavelength laser light is used in water jet laser processing, there is a problem that the substrate of the adhesive tape breaks during water jet laser processing, or the substrate becomes fragile during water jet laser processing, and the substrate is easily broken during the expanding process. This is the same whether the substrate of the adhesive tape is a resin film or a porous substrate.
[0010] The present disclosure has been made in consideration of the above-mentioned situation, and has as its main object to provide an adhesive tape for processing electronic components, which has a substrate with good expandability and can suppress breakage of the substrate during water jet laser processing and expansion. [Means for solving the problem]
[0011] One embodiment of the present disclosure provides an adhesive tape for electronic component processing having a resin film and an adhesive layer disposed on a first surface of the resin film, wherein the elongation at break of the adhesive tape for electronic component processing after water jet laser processing of the adhesive tape for electronic component processing is 50% or more.
[0012] Another embodiment of the present disclosure is an adhesive tape for electronic component processing having a resin film and an adhesive layer disposed on a first surface of the resin film, the resin film having a thickness of 100 μm or more, and a storage modulus of the resin film at 100° C. of 1×10 7 The present invention provides an adhesive tape for processing electronic components, the adhesive tape having a laser beam absorption coefficient of 100 Pa or more, the resin film being non-absorbent to laser beams, and the resin film having an elongation at break of 500% or more.
[0013] Another embodiment of the present disclosure provides a method for manufacturing electronic components, comprising: an application step of applying the above-mentioned adhesive tape for electronic component processing to a first surface of a workpiece substrate; a dicing step of cutting the workpiece substrate into a plurality of chips with a laser guided by a water jet; an expanding step of stretching the adhesive tape for electronic component processing to increase the spacing between the chips; and a pick-up step of picking up the chips from the adhesive tape for electronic component processing. Effect of the Invention
[0014] The present disclosure can provide an adhesive tape for processing electronic components, which has a substrate with good expandability and can suppress breakage of the substrate during water jet laser processing and expansion. [Brief description of the drawings]
[0015] [Figure 1] 1 is a schematic cross-sectional view illustrating an example of an adhesive tape for processing electronic components according to the present disclosure. [Diagram 2] FIG. 1 is a schematic diagram illustrating a method for preparing a test piece used to measure elongation at break after water jet laser processing. [Diagram 3] 1A to 1C are process diagrams illustrating a method for manufacturing an electronic component according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The following describes the embodiments of the present disclosure with reference to the drawings. However, the present disclosure can be implemented in many different forms and should not be limited to the description of the embodiments exemplified below. In addition, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the actual form in order to make the explanation clearer, but these are merely examples and should not be interpreted as being limited. In this specification and each figure, the same reference numerals are used to designate elements similar to those described above with respect to the previous figures, and detailed descriptions may be omitted as appropriate.
[0017] In this specification, when describing an aspect in which another component is disposed on a certain component, the term "above" or "below" includes both cases in which another component is disposed directly above or below a certain component so as to be in contact with the component, and cases in which another component is disposed above or below a certain component with another component interposed therebetween, unless otherwise specified. In addition, in this specification, when describing an aspect in which another component is disposed on the surface of a certain component, the term "on the surface" includes both cases in which another component is disposed directly above or below a certain component so as to be in contact with the component, and cases in which another component is disposed above or below a certain component with another component interposed therebetween, unless otherwise specified.
[0018] In this specification, the term "sheet" also includes a member called a "film."
[0019] The adhesive tape for processing electronic components and the method for producing electronic components according to the present disclosure will be described below.
[0020] A. Adhesive tape for electronic parts processing The pressure-sensitive adhesive tape for processing electronic components according to the present disclosure has two embodiments, each of which will be described below.
[0021] I. First embodiment A first embodiment of the adhesive tape for electronic component processing in the present disclosure is an adhesive tape for electronic component processing having a resin film and an adhesive layer arranged on a first surface of the resin film, wherein the elongation at break of the adhesive tape for electronic component processing after water jet laser processing of the adhesive tape for electronic component processing is 50% or more.
[0022] 1 is a schematic cross-sectional view illustrating an example of an adhesive tape for electronic component processing according to this embodiment. As illustrated in Fig. 1, an adhesive tape for electronic component processing 10 has a resin film 1 and an adhesive layer 2 disposed on a first surface of the resin film 1.
[0023] In this embodiment, the elongation at break of the adhesive tape for electronic component processing after the water jet laser processing of the adhesive tape for electronic component processing is a predetermined value or more, so that the breakage of the resin film during the water jet laser processing can be suppressed. In addition, since the resin film can be prevented from becoming brittle during the water jet laser processing, the breakage of the resin film during the subsequent expansion can also be suppressed. Furthermore, if the elongation at break of the adhesive tape for electronic component processing after the water jet laser processing of the adhesive tape for electronic component processing is a predetermined value or more, it can be said that the expandability of the resin film is good.
[0024] Therefore, the adhesive tape for electronic component processing of this embodiment can be suitably used when dicing a substrate to be processed by water jet laser processing.
[0025] Hereinafter, each component of the adhesive tape for processing electronic parts according to this embodiment will be described.
[0026] 1. Resin film The resin film in this embodiment is a member that supports the adhesive layer.
[0027] (1) Characteristics of resin film In this embodiment, the elongation at break of the adhesive tape for electronic component processing after the water jet laser processing of the adhesive tape for electronic component processing is 50% or more, may be 100% or more, or may be 200% or more. When the elongation at break after the water jet laser processing is in the above range, the break of the resin film during the water jet laser processing and the expansion can be suppressed. In addition, when the elongation at break after the water jet laser processing is in the above range, it can be said that the expandability of the resin film is good. On the other hand, the upper limit of the elongation at break after the water jet laser processing is not particularly limited.
[0028] The elongation at break of the adhesive tape for processing electronic components after the adhesive tape for processing electronic components is measured by the following method.
[0029] First, water jet laser processing is performed on the adhesive tape for electronic component processing. First, as shown in FIG. 2, the adhesive tape for electronic component processing 10 is cut into a size of 30 mm x 60 mm. Next, the adhesive tape for electronic component processing 10 is placed on a glass plate 51 so that the resin film faces the glass plate side and the adhesive layer faces outward, and is fixed with Kapton tape 52 to obtain a laminate for processing 50. Using a dicing device for water jet laser processing, 10 passes (5 round trips) are made on the same location of the laminate for processing 50 from the adhesive layer side as shown by the arrow in FIG. 2 under the following conditions. Next, as shown by the dashed line in FIG. 2, the center of the adhesive tape for electronic component processing 10 is cut into a width of 10 mm using a cutter to obtain a strip-shaped test piece 53 to be used in the tensile test described later. The dicing device for water jet laser processing is SYNOVA's "Laser Microjet".
[0030] <Water jet laser processing conditions> Laser wavelength: 532nm Cutting speed: 100mm / s Laser beam diameter (water jet diameter): 50μm Water pressure: 25MPa Average Power: 6.6W Frequency: 700Hz Pulse width: 180μsec
[0031] In addition, when measuring the elongation at break of the adhesive tape for electronic component processing after water jet laser processing of the adhesive tape for electronic component processing, a wavelength of 532 nm, which is the second harmonic of a YAG laser, is used as an example of a short wavelength laser.
[0032] Next, the elongation at break of the adhesive tape for electronic component processing after the water jet laser processing of the adhesive tape for electronic component processing is measured. The elongation at break of the adhesive tape for electronic component processing is measured in accordance with JIS K7127:1999. Specific measurement conditions are shown below. For example, the tensile tester used is "Tensilon RTF1150" manufactured by A&D Co., Ltd.
[0033] <Measurement conditions> Test piece: rectangular test piece (width 10mm, length 60mm) ·Distance between gauge lines: 25mm Initial distance between chucks: 25mm Pulling speed: 200mm / min ·Temperature: 23±2℃ ·Humidity: 50±10%RH
[0034] Methods for controlling the elongation at break of the adhesive tape for electronic component processing after water jet laser processing of the adhesive tape for electronic component processing include, for example, a method of adjusting the thickness of the resin film, a method of adjusting the storage modulus of the resin film at high temperatures, a method of adjusting the initial elongation at break of the adhesive tape for electronic component processing, and a method of using a resin film that is non-absorbent to laser light.
[0035] When the resin film is thick, the resin film is less damaged by the laser light than when it is thin, so the elongation at break of the adhesive tape for electronic component processing after water jet laser processing tends to be large. On the other hand, when the resin film is thin, the resin film is more damaged by the laser light than when it is thick, so the elongation at break of the adhesive tape for electronic component processing after water jet laser processing tends to be small, or the resin film tends to break easily during water jet laser processing. The thickness of the resin film will be described later.
[0036] In water jet laser processing, heat is generated instantaneously when the substrate to be processed is diced, and the heat is also transmitted to the adhesive tape for electronic component processing. In this state, the adhesive tape for electronic component processing is subjected to the water jet. Therefore, if the adhesive tape for electronic component processing becomes soft due to heat, it is considered that the adhesive tape for electronic component processing is easily damaged by the water pressure of the water jet. On the other hand, if the adhesive tape for electronic component processing is relatively hard even when heated, it is considered that damage to the adhesive tape for electronic component processing caused by the water pressure of the water jet can be reduced. Here, the storage modulus can be used as an index of hardness. Therefore, if the storage modulus of the resin film at high temperatures is large, the elongation at break of the adhesive tape for electronic component processing after water jet laser processing tends to be large. On the other hand, if the storage modulus of the resin film at high temperatures is small, the elongation at break of the adhesive tape for electronic component processing after water jet laser processing tends to be small, or the resin film tends to be easily broken during water jet laser processing. The storage modulus of the resin film at high temperatures will be described in the second embodiment described later.
[0037] If the elongation at break of the adhesive tape for electronic component processing before water jet laser processing, i.e., the initial elongation at break of the adhesive tape for electronic component processing, is large, the elongation at break of the adhesive tape for electronic component processing after water jet laser processing tends to be large. On the other hand, if the elongation at break of the adhesive tape for electronic component processing initially is small, the elongation at break of the adhesive tape for electronic component processing after water jet laser processing tends to be small, or the adhesive tape for electronic component processing tends to be easily broken during water jet laser processing.
[0038] By using a resin film that is non-absorbent to the laser light used in water jet laser processing, it is possible to prevent the resin film from absorbing the laser light and generating heat. This can prevent the adhesive tape for electronic component processing from breaking during water jet laser processing, or prevent the resin film from becoming brittle during water jet laser processing. On the other hand, if a resin film that is absorbent to the laser light used in water jet laser processing is used, the resin film will absorb the laser light, generate heat, and be cut. The fact that the resin film is non-absorbent to the laser light will be described in the second embodiment below.
[0039] (2) Resin film material The material of the resin film is not particularly limited as long as it satisfies the elongation at break of the adhesive tape for electronic component processing after the water jet laser processing. Among them, polypropylene, polyester elastomer, and thermoplastic polyurethane (TPU) are preferable. These may be used alone or in combination of two or more.
[0040] The resin film may contain additives as necessary, such as plasticizers, fillers, antioxidants, light stabilizers, antistatic agents, lubricants, dispersants, flame retardants, and colorants.
[0041] As described below, when the adhesive layer is an energy ray-curable adhesive layer, it is preferable in the pick-up process to reduce the adhesive strength of the adhesive layer by irradiating energy rays from the resin film side of the adhesive tape for electronic component processing to cure the adhesive layer, and therefore it is preferable that the resin film is transparent to energy rays.
[0042] The resin film may be, for example, a single layer or a multilayer.
[0043] The surface of the resin film on the adhesive layer side may be subjected to a surface treatment in order to improve adhesion to the adhesive layer. The surface treatment is not particularly limited, and examples thereof include corona treatment, plasma treatment, ozone treatment, frame treatment, primer treatment, vapor deposition treatment, and alkali treatment.
[0044] The resin film may be a stretched film or a non-stretched film. Of these, the resin film is preferably a non-stretched film, which can improve the expandability.
[0045] (3) Thickness of the resin film The thickness of the resin film is not particularly limited as long as it satisfies the elongation at break after the water jet laser processing. The thickness of the resin film is preferably 100 μm or more, and may be 150 μm or more. By having the thickness of the resin film in the above range, the elongation at break after the water jet laser processing can be easily adjusted to be within a predetermined range. On the other hand, the thickness of the resin film is, for example, 1000 μm or less, may be 500 μm or less, or may be 300 μm or less. If the thickness of the resin film is within the above range, the expandability of the resin film is good. Specifically, the thickness of the resin film is 100 μm or more and 1000 μm or less, may be 100 μm or more and 500 μm or less, may be 150 μm or more and 500 μm or less, or may be 150 μm or more and 300 μm or less.
[0046] The thickness of the resin film is measured using a thickness gauge such as a dial thickness gauge or a digital thickness gauge, and the arithmetic average value of the thicknesses at 10 randomly selected points is taken as the thickness.
[0047] When measuring the thickness of the resin film, the adhesive layer is removed from the adhesive tape for electronic component processing, and the resin film is taken out. As a method for removing the adhesive layer, a method of dissolving the adhesive layer with a solvent can be mentioned. As the solvent, the solvent contained in the adhesive composition used for forming the adhesive layer can be used. In addition, when a primer layer is disposed on the adhesive layer side of the resin film, the primer layer is also removed when measuring the thickness of the resin film. The method for removing the primer layer is the same as the method for removing the adhesive layer.
[0048] 2. Adhesive layer The adhesive layer in this embodiment is not particularly limited as long as it can sufficiently fix the workpiece substrate and chips to the adhesive tape for electronic component processing during dicing, and can easily peel the chips from the adhesive tape for electronic component processing during pick-up.
[0049] In addition, the adhesive layer is preferably non-absorbent to the laser light used in the water jet laser processing. By making the adhesive layer non-absorbent to the laser light, the adhesive layer can be prevented from absorbing the laser light, generating heat, and being cut. Therefore, the adhesive layer can reduce the force of the water jet. This can prevent chipping and chipping caused by splashing of water during water jet laser processing.
[0050] Examples of the adhesive layer include an energy ray curable adhesive layer having energy ray curability and a slightly adhesive layer exhibiting slightly adhesive properties. Among them, an energy ray curable adhesive layer is preferred. An energy ray curable adhesive layer can increase the initial adhesive strength. This allows the substrate and chip to be sufficiently fixed to the adhesive tape for electronic component processing during dicing by water jet laser processing. Each adhesive layer will be described below.
[0051] (1) Energy ray curable adhesive layer The energy ray curable adhesive layer is an adhesive layer whose adhesive strength is reduced by irradiation with energy rays. In the energy ray curable adhesive layer, the initial adhesive strength of the adhesive layer during dicing allows the substrate and chips to be sufficiently fixed to the adhesive tape for electronic component processing. Furthermore, during pick-up, the adhesive strength is reduced by irradiation with energy rays, improving the peelability, allowing the chips to be easily peeled off from the adhesive tape for electronic component processing.
[0052] Examples of the energy ray include light rays such as far ultraviolet rays, ultraviolet rays, near ultraviolet rays, and infrared rays, electromagnetic waves such as X-rays and gamma rays, as well as electron beams, proton beams, neutron beams, etc. Among these, from the viewpoint of versatility, etc., ultraviolet rays and electron beams are preferred, and ultraviolet rays are more preferred.
[0053] The energy ray curable adhesive layer is not particularly limited as long as it satisfies the adhesive properties described below, and may contain, for example, at least a resin (adhesive base) and an energy ray curable compound. When the adhesive layer contains an energy ray curable compound, the adhesive strength can be reduced by curing the energy ray curable compound by irradiation with energy rays, and at this time, the cohesive strength is increased, making it easier to peel off.
[0054] (a) Resin (main adhesive) Examples of the resin (adhesive base) include resins that are generally used as adhesive bases, such as acrylic resins, polyester resins, polyimide resins, and silicone resins. Among these, acrylic resins are preferred. By using acrylic resins, adhesive residue on the adherend can be reduced.
[0055] Therefore, the adhesive layer preferably contains at least an acrylic resin, an energy ray curable compound, and a crosslinking agent. In the adhesive layer, the acrylic resin is usually present as a crosslinked body formed by crosslinking between acrylic resins with the crosslinking agent, but the acrylic resin may be present as a single unit together with the crosslinked body.
[0056] (Acrylic resin) The acrylic resin is not particularly limited, and examples thereof include (meth)acrylic acid ester polymers obtained by homopolymerizing (meth)acrylic acid esters, and (meth)acrylic acid ester copolymers obtained by copolymerizing (meth)acrylic acid esters with other monomers, with (meth)acrylic acid esters as the main component. Among these, (meth)acrylic acid ester copolymers are preferred. Specific examples of (meth)acrylic acid esters and other monomers include those disclosed in JP 2012-31316 A. The other monomers can be used alone or in combination of two or more kinds. The main component here means that the copolymerization ratio is 51% by mass or more, and preferably 65% by mass or more.
[0057] Among these, as the acrylic resin, a (meth)acrylic acid ester copolymer having a (meth)acrylic acid ester as the main component and obtained by copolymerizing the (meth)acrylic acid ester with a hydroxyl group-containing monomer copolymerizable with the (meth)acrylic acid ester, or a (meth)acrylic acid ester copolymer having a (meth)acrylic acid ester as the main component and obtained by copolymerizing a hydroxyl group-containing monomer and a carboxyl group-containing monomer copolymerizable with the (meth)acrylic acid ester can be preferably used.
[0058] In this specification, (meth)acrylic acid refers to at least one of acrylic acid and methacrylic acid.
[0059] The copolymerizable hydroxyl group-containing monomer and carboxyl group-containing monomer are not particularly limited, and for example, the hydroxyl group-containing monomer and carboxyl group-containing monomer disclosed in JP-A-2012-31316 can be used.
[0060] The weight average molecular weight of the acrylic resin is, for example, preferably from 200,000 to 1,000,000, and more preferably from 200,000 to 800,000. By setting the weight average molecular weight of the acrylic resin within the above range, sufficient initial adhesive strength can be exhibited.
[0061] Here, in this specification, the weight average molecular weight is a polystyrene-equivalent value measured by gel permeation chromatography (GPC). The weight average molecular weight is measured, for example, by using HLC-8220GPC manufactured by Tosoh Corporation as a measuring device, TSKGEL-SUPERMULTIPORE-HZ-M manufactured by Tosoh Corporation as a column, THF as a solvent, and standard polystyrenes with molecular weights of 1050, 5970, 18100, 37900, 96400, and 706000 as standards.
[0062] In addition, when the acrylic resin is a (meth)acrylic acid ester copolymer of a hydroxyl group-containing monomer and a carboxyl group-containing monomer copolymerizable with the (meth)acrylic acid ester, the mass ratio of the hydroxyl group-containing monomer to the carboxyl group-containing monomer is, for example, preferably 51:49 to 100:0, and more preferably 75:25 to 100:0. If the mass ratio of each monomer is within the above range, an effective decrease in adhesive strength due to energy ray irradiation can be expected, and the occurrence of adhesive residue can be suppressed.
[0063] The acrylic resin may be energy ray curable, for example, may have an energy ray curable functional group in a side chain. The energy ray curable functional group preferably has, for example, an ethylenically unsaturated bond, and specific examples thereof include a (meth)acryloyl group, a vinyl group, and an allyl group.
[0064] (b) Energy ray curable compound The energy ray-curable compound is not particularly limited as long as it is polymerizable upon irradiation with energy rays, and examples thereof include compounds having an energy ray-curable functional group.
[0065] Examples of the energy ray curable compound include energy ray curable monomers, energy ray curable oligomers, and energy ray curable polymers. The energy ray curable polymers are polymers different from the above-mentioned resins (adhesive bases). Among them, energy ray curable oligomers are preferred from the viewpoint of the balance of adhesive strength before and after energy ray irradiation. Also, energy ray curable monomers, energy ray curable oligomers, and energy ray curable polymers may be used in combination. For example, when an energy ray curable monomer is used in addition to an energy ray curable oligomer, the adhesive layer is cured by three-dimensional crosslinking when irradiated with energy rays, thereby reducing the adhesive strength, and the cohesive strength is increased to prevent transfer to the chip side.
[0066] Examples of the energy ray curable compound include radical polymerizable compounds, cationic polymerizable compounds, and anionic polymerizable compounds. Among them, radical polymerizable compounds are preferred. They have a high curing speed, can be selected from a wide variety of compounds, and can easily control physical properties such as adhesive strength before and after energy ray irradiation.
[0067] In addition, the adhesive strength after the energy ray irradiation can be controlled by adjusting the number of energy ray curable functional groups of the energy ray curable compound. As described above, for example, when the number of energy ray curable functional groups is increased, the crosslink density of the adhesive layer after the energy ray irradiation tends to be increased, and the adhesive strength after the energy ray irradiation tends to be decreased.
[0068] In the energy ray curable compound, the number of energy ray curable functional groups is preferably 2 or more in one molecule, more preferably 3 or more in one molecule, and even more preferably 4 or more. If the number of energy ray curable functional groups is within the above range, the crosslink density of the adhesive layer after irradiation with energy rays is sufficient, so that the desired peelability can be achieved. In addition, the occurrence of adhesive residue due to a decrease in cohesive force can be suppressed. In addition, the upper limit of the number of energy ray curable functional groups is not particularly limited.
[0069] The energy ray curable compound is preferably a radical polymerizable oligomer, more preferably a radical polymerizable polyfunctional oligomer. Examples of the radical polymerizable oligomer include those disclosed in JP2012-31316A.
[0070] In addition, as the energy ray curable compound, a radical polymerizable oligomer and a radical polymerizable monomer may be used, and among them, a radical polymerizable polyfunctional oligomer and a radical polymerizable polyfunctional monomer may be used. As the radical polymerizable monomer, for example, those disclosed in JP2010-173091A may be used.
[0071] Examples of the energy ray curable compound include (meth)acrylate monomers, (meth)acrylate oligomers, (meth)acrylate polymers, etc. Examples of the energy ray curable compound that can be used include urethane (meth)acrylate, polyester (meth)acrylate, epoxy (meth)acrylate, etc.
[0072] In addition, the energy ray curable compound may be a commercially available product. For example, urethane acrylate "Shikoh UV7620EA (molecular weight: 4100)" manufactured by Mitsubishi Chemical Corporation, urethane acrylates "Art Resin UN-905 (molecular weight: 50000 to 210000)", "Art Resin UN-905DU1 (molecular weight: 26000)", "Art Resin UN-951SC (molecular weight: 12500)", "Art Resin UN-952 (molecular weight: 6500 to 9500)", "Art Resin UN-953 (molecular weight: 14000 to 40000)", "Art Resin UN-954 (molecular weight: 4200)", and "Art Resin H-219 (molecular weight: 10000 to 15000)" manufactured by Negami Chemical Industries, Ltd. Examples of suitable polymers include "Art Resin H-315M (molecular weight: 6600)" and "Art Resin H-417M (molecular weight: 4000)" manufactured by Taisei Fine Chemical Co., Ltd., "8BR-600 (molecular weight: 100000)" acrylic urethane polymer manufactured by Taisei Fine Chemical Co., Ltd., "Unidic V-6850" polymer acrylate manufactured by DIC Corporation, "SMP-250AP (molecular weight: 20000-30000)" and "SMP-360A (molecular weight: 20000-30000)" manufactured by Kyoeisha Chemical Co., Ltd., and "HA7975" acrylic resin acrylate manufactured by Showa Denko Materials Co., Ltd.
[0073] The energy ray-curable compounds may be used alone or in combination of two or more kinds.
[0074] The weight average molecular weight of the energy ray curable compound is not particularly limited, but is preferably 30,000 or less, more preferably 10,000 or less, and even more preferably 8,000 or less. If the weight average molecular weight of the energy ray curable compound is within the above range, it exhibits sufficient compatibility with the acrylic resin (adhesive base agent), and the adhesive layer exhibits the desired adhesive strength before energy ray irradiation, and after energy ray irradiation, the occurrence of adhesive residue is suppressed and it can be easily peeled off. On the other hand, the weight average molecular weight of the energy ray curable resin composition is, for example, 500 or more.
[0075] In addition, the adhesive strength after irradiation with energy rays can be controlled by adjusting the content of the energy ray-curable compound. If the content of the energy ray-curable compound is high, the adhesive strength after irradiation with energy rays tends to be low.
[0076] The content of the energy ray curable compound is, for example, preferably 5 parts by mass or more and 150 parts by mass or less, more preferably 20 parts by mass or more and 100 parts by mass or less, and even more preferably 50 parts by mass or more and 80 parts by mass or less, relative to 100 parts by mass of the resin (main adhesive agent). If the content of the energy ray curable compound is within the above range, the crosslink density of the adhesive layer after irradiation with energy rays is sufficient, so that the desired peelability can be achieved. In addition, the occurrence of adhesive residue due to a decrease in cohesive force can be suppressed.
[0077] (c) Polymerization initiator The adhesive layer may contain a polymerization initiator in addition to the resin (main adhesive agent) and the energy ray-curable compound.
[0078] As the polymerization initiator, a general photopolymerization initiator can be used. Specifically, acetophenones, benzophenones, α-hydroxyketones, benzyl methyl ketals, α-aminoketones, and bisacylphosphine oxides can be mentioned. When urethane acrylate is used as the energy ray curable compound, the polymerization initiator is preferably a bisacylphosphine-based polymerization initiator. Since this polymerization initiator has heat resistance, even when the adhesive layer is irradiated with energy rays through a mesh sheet, the energy ray curable compound can be reliably cured.
[0079] The polymerization initiator preferably has an absorption at a wavelength of 230 nm or more, and preferably has an absorption at a wavelength of 300 nm or more and 400 nm or less. Such a polymerization initiator can efficiently generate active species that absorb a wide energy ray with a wavelength of 300 nm or more and induce a polymerization reaction of the energy ray curable compound. Therefore, even with a small amount of energy ray irradiation, the energy ray curable compound can be efficiently cured and easily peeled off. In addition, as described above, resins and the like can be used for the mesh sheet, and many resins absorb energy rays with a wavelength of up to about 300 nm, but transmit energy rays with a wavelength of about 300 nm or more. Furthermore, in recent years, LED lamps with a wavelength of 300 nm or more are often used in energy ray irradiation devices. Therefore, by using a polymerization initiator with an absorption at a wavelength of 230 nm or more, the energy ray curable compound can be cured using the energy rays that have transmitted through the mesh sheet.
[0080] The content of the polymerization initiator is, for example, preferably 0.01 parts by mass or more and 10 parts by mass or less, more preferably 0.5 parts by mass or more and 6 parts by mass or less, based on the total of 100 parts by mass of the resin (adhesive base) and the energy ray curable compound. If the content of the polymerization initiator is less than the above range, the polymerization reaction of the energy ray curable compound does not occur sufficiently, and the adhesive strength of the adhesive layer after the energy ray irradiation becomes excessively high, and peelability may not be realized. On the other hand, if the content of the polymerization initiator exceeds the above range, the energy ray may only reach the vicinity of the energy ray irradiated surface, and the adhesive layer may not be cured sufficiently. In addition, the cohesive force may decrease, which may cause the occurrence of glue residue.
[0081] (d) Crosslinking agent The adhesive layer may contain a crosslinking agent in addition to the resin (main adhesive agent) and the energy ray-curable compound.
[0082] The crosslinking agent is not particularly limited as long as it crosslinks at least between resins (main adhesives), and is appropriately selected according to the type of resin (main adhesive). For example, isocyanate-based crosslinking agents, epoxy-based crosslinking agents, metal chelate-based crosslinking agents, etc. are included. Specific examples of isocyanate-based crosslinking agents and epoxy-based crosslinking agents include those disclosed in JP2012-31316A. The crosslinking agents can be used alone or in combination of two or more.
[0083] The content of the crosslinking agent is appropriately set according to the type of the crosslinking agent, and is preferably 0.01 to 15 parts by mass, more preferably 0.01 to 10 parts by mass, relative to 100 parts by mass of the resin (main adhesive agent). If the content of the crosslinking agent is less than the above range, the adhesion may be poor, or the adhesive layer may undergo cohesive failure when peeling off the chip, resulting in adhesive residue. On the other hand, if the content of the crosslinking agent exceeds the above range, the crosslinking agent may remain in the adhesive layer as an unreacted monomer after irradiation with energy rays, which may cause adhesive residue due to a decrease in cohesive force.
[0084] (e) Additives The adhesive layer may contain various additives as necessary, such as a tackifier, an antistatic agent, a plasticizer, a silane coupling agent, a metal chelating agent, a surfactant, an antioxidant, an ultraviolet absorbing agent, a colorant, a preservative, an antifoaming agent, and a wettability adjusting agent.
[0085] (f) Other The energy ray curable adhesive layer can be formed, for example, by applying an adhesive composition onto a resin film or a separator. When the adhesive layer is formed on a separator, a resin film is placed on the adhesive layer after the adhesive layer is formed, thereby obtaining an adhesive tape for electronic component processing having the resin film, adhesive layer, and separator in this order.
[0086] (2) Slightly adhesive adhesive layer The weakly adhesive type pressure-sensitive adhesive layer is an adhesive layer that exhibits weak adhesion.
[0087] Although the initial adhesive strength of the low-tack adhesive layer is low, it can adequately fix the substrate and chips to the adhesive tape for electronic component processing during dicing. In addition, because the initial adhesive strength is low, it has excellent removability, and the chips can be easily peeled off from the adhesive tape for electronic component processing during pick-up.
[0088] Here, the weak adhesive layer exhibiting weak adhesion means that the adhesive layer exhibits sufficient adhesive strength to sufficiently fix the workpiece substrate and chip to the adhesive tape for electronic component processing during dicing, and to such an extent that the chip can be easily peeled off from the adhesive tape for electronic component processing during pick-up.
[0089] The weak adhesive layer is not particularly limited as long as it satisfies the adhesive properties described below. In particular, the weak adhesive layer preferably contains at least an acrylic resin, and more preferably contains an acrylic resin and a crosslinking agent.
[0090] Here, the term "the low-adhesive adhesive layer contains an acrylic resin" means that the acrylic resin may exist in the low-adhesive adhesive layer as a single entity without forming crosslinks, or as a crosslinked entity formed by crosslinking between acrylic resins or between an acrylic resin and another resin, or both the single entity and the crosslinked entity may be present.
[0091] Here, the adhesive layer containing an acrylic resin means that the acrylic resin may exist in the adhesive layer as a single entity without forming crosslinks, or as a crosslinked body formed by crosslinking between acrylic resins or between an acrylic resin and another resin, or both the single entity and the crosslinked body may be present.
[0092] (a) Acrylic resin The acrylic resin is not particularly limited, and examples thereof include a (meth)acrylic acid ester polymer obtained by homopolymerizing a (meth)acrylic acid ester, and a (meth)acrylic acid ester copolymer obtained by copolymerizing a (meth)acrylic acid ester as a main component with a (meth)acrylic acid ester and other monomers. Among these, the (meth)acrylic acid ester copolymer is preferred.
[0093] Here, in the (meth)acrylic acid ester copolymer, the (meth)acrylic acid ester is the main component, which means that the proportion of the (meth)acrylic acid ester relative to other monomers in the copolymer is more than 30 mass%, and specifically, the copolymerization proportion is 51 mass% or more.
[0094] In this specification, (meth)acrylic acid refers to at least one of acrylic acid and methacrylic acid.
[0095] As the (meth)acrylic acid ester, a (meth)acrylic acid alkyl ester such as a linear or branched alkyl ester having 1 to 30 carbon atoms, a (meth)acrylic acid cycloalkyl ester, etc. can be used. Specific examples of the (meth)acrylic acid alkyl ester include those disclosed in JP 2014-101457 A. The (meth)acrylic acid ester may contain one or more kinds. Among them, a (meth)acrylic acid ester having 1 to 18 carbon atoms, particularly a (meth)acrylic acid ester having 1 to 8 carbon atoms, is preferred. The glass transition temperature of the acrylic resin is likely to be within the range described below, and the adhesiveness of the adhesive layer can be improved.
[0096] The acrylic resin may be a copolymer of a (meth)acrylic acid ester and a monomer or oligomer. In addition to the (meth)acrylic acid ester, other monomers or oligomers may be included as copolymerization components as necessary to improve the cohesive strength, heat resistance, and the like. Examples of the copolymerization components include functional group-containing (meth)acrylates that are copolymerizable with the (meth)acrylic acid ester. Specific examples include carboxyl group-containing monomers, acid anhydride group-containing monomers, hydroxyl group-containing monomers, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, epoxy group-containing monomers, vinyl esters, vinyl ethers, and aromatic vinyl compounds. In addition, nitrogen-containing monomers such as cyano group-containing monomers, amide group-containing monomers, amino group-containing monomers, and isocyanate group-containing monomers may be used as copolymerization components. The copolymerization components may be included in the acrylic acid ester polymer as copolymerization components.
[0097] The weight average molecular weight of the acrylic resin is, for example, preferably 100,000 to 2,000,000, more preferably 200,000 to 1,000,000, and even more preferably 400,000 to 800,000. If the weight average molecular weight is smaller than the above range, there is a possibility that adhesive residue will occur in the adhesive layer. On the other hand, if the weight average molecular weight is larger than the above range, there is a possibility that the adhesive strength will be high and the peelability will be reduced.
[0098] The glass transition temperature of the acrylic resin is, for example, preferably −100° C. or higher and 0° C. or lower, and more preferably −80° C. or higher and −20° C. or lower. By using an acrylic resin having a glass transition temperature in the above range as the base resin, it becomes easier to obtain the desired adhesive properties.
[0099] The glass transition temperature of the acrylic resin can be appropriately adjusted by changing the type of monomer unit used, the ratio of the monomer units to be combined, etc. Even in the case of a polymer (homopolymer) obtained by homopolymerizing a monomer, the glass transition temperature of the acrylic resin may be within the above range. However, the use of a monomer unit whose homopolymer glass transition temperature is not within the above range is not limited. It is sufficient that the glass transition temperature of a copolymer obtained by copolymerizing a combination of various monomer units is within the above range.
[0100] In this specification, the glass transition temperature means a value measured by a method based on the peak top value of the loss tangent (tan δ) (DMA method). The loss tangent is determined by the value of the loss modulus / storage modulus. These moduli are measured by using a dynamic viscoelasticity measuring device to measure the stress when a force is applied to a polymer or copolymer at a certain frequency.
[0101] The acrylic resin can be obtained by polymerizing a monomer such as the above-mentioned (meth)acrylic acid ester, monomer, or oligomer by a conventional method such as solution polymerization, bulk polymerization, emulsion polymerization, or suspension polymerization.
[0102] (b) Crosslinking agent The crosslinking agent may be any crosslinking agent capable of crosslinking the acrylic resin, and may be any commonly used crosslinking agent, such as an epoxy crosslinking agent, an isocyanate crosslinking agent, a metal chelate crosslinking agent, or a carbodiimide crosslinking agent.
[0103] The content of the crosslinking agent is, for example, 0.1 parts by mass or more and 20 parts by mass or less, preferably 0.3 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the acrylic resin. By having the content of the crosslinking agent within the above range, it becomes easier to obtain the desired adhesive properties.
[0104] (c) Other ingredients The adhesive layer may contain any additives, as necessary, such as a lubricant, a plasticizer, a filler, an antistatic agent, an antiblocking agent, a light stabilizer, a colorant, and the like.
[0105] (d) Other The method for forming the weakly adhesive layer is the same as the method for forming the energy ray curable adhesive layer.
[0106] (3) Thickness of adhesive layer The thickness of the adhesive layer may be any thickness that provides a desired adhesive strength, and may be, for example, 50 μm or more, or 100 μm or more. If the thickness of the adhesive layer is within the above range, the water permeability can be reduced, and chipping or chipping caused by water splashing during water jet laser processing can be suppressed. On the other hand, the thickness of the adhesive layer may be, for example, 300 μm or less, or 200 μm or less. When the adhesive layer is an energy ray curable adhesive layer, if the thickness of the adhesive layer is within the above range, the adhesive layer can be sufficiently cured by irradiation with energy rays. Specifically, the thickness of the adhesive layer may be 50 μm or more and 300 μm or less, or 100 μm or more and 200 μm or less.
[0107] 3. Other configurations The adhesive tape for processing electronic parts of this embodiment may have other components, if necessary, in addition to the above-mentioned resin film and adhesive layer.
[0108] The adhesive tape for processing electronic parts of this embodiment may have a separator on the surface of the adhesive layer opposite to the resin film.
[0109] 4. Characteristics of adhesive tapes for electronic component processing When the adhesive layer is an energy ray curable adhesive layer, the adhesive strength of the adhesive tape for electronic component processing to a glass plate before energy ray irradiation may be, for example, 0.5 N / 25 mm or more and 40 N / 25 mm or less. The adhesive strength of the adhesive tape to a glass plate after energy ray irradiation is, for example, preferably 2.0 N / 25 mm or less. The lower limit of the adhesive strength to a glass plate after energy ray irradiation is not particularly limited, and is, for example, 0.01 N / 25 mm or more.
[0110] When the adhesive layer is a weak adhesive layer, the adhesive strength of the adhesive tape for electronic component processing to a glass plate is 6.0 N / 25 mm or less, may be 3.0 N / 25 mm or less, or may be 0.5 N / 25 mm or less. On the other hand, the adhesive strength to a glass plate is, for example, 0.05 N / 25 mm or more.
[0111] The adhesive strength to glass plates is measured according to JIS Z0237:2022 (Adhesive tape and adhesive sheet test method) method 1 (temperature 23°C, humidity 50%, tape and sheet peeled at 180° to stainless steel test plate), by peeling the test piece in the length direction under the conditions of width 25mm, peel angle 180°, and peel speed 300mm / min. The glass plate used is float glass (size 150mm x 70mm, thickness 2mm) manufactured by Osaka Glass Industry Co., Ltd.
[0112] The adhesive strength to a glass plate after irradiation with energy rays is measured after the energy ray-curable adhesive layer is cured by irradiating it with energy rays. For example, the adhesive strength to a glass plate is measured by irradiating the adhesive tape with an integrated light dose of 500 mJ / cm from the resin film side of the adhesive tape for processing electronic components. 2 The energy ray curable adhesive layer is cured by irradiating it with ultraviolet light so as to obtain the above-mentioned result.
[0113] 5.Applications The adhesive tape for electronic component processing of this embodiment can be used as a dicing tape. In particular, the adhesive tape for electronic component processing of this embodiment can be suitably used as a dicing tape when dicing a substrate to be processed by laser processing. In particular, the adhesive tape for electronic component processing of this embodiment can be suitably used as a dicing tape when dicing a substrate to be processed by water jet laser processing.
[0114] II. Second embodiment A second embodiment of the adhesive tape for electronic component processing in the present disclosure is an adhesive tape for electronic component processing having a resin film and an adhesive layer disposed on a first surface of the resin film, the resin film having a thickness of 100 μm or more, and the storage modulus of the resin film at 100° C. is 1×10 7 Pa or more, the resin film is non-absorbent to laser light, and the elongation at break of the resin film is 500% or more.
[0115] 1 is a schematic cross-sectional view illustrating an example of an adhesive tape for electronic component processing according to this embodiment. As illustrated in Fig. 1, an adhesive tape for electronic component processing 10 has a resin film 1 and an adhesive layer 2 disposed on a first surface of the resin film 1.
[0116] In this embodiment, the resin film has a thickness of a predetermined value or more, the storage modulus of the resin film at 100°C is a predetermined value or more, the resin film is non-absorbent to laser light, and the elongation of the resin film at break is a predetermined value or more, so that the breakage of the resin film during water jet laser processing can be suppressed. In addition, the resin film has a thickness of a predetermined value or more, the storage modulus of the resin film at 100°C is a predetermined value or more, and the resin film is non-absorbent to laser light, so that the resin film can be prevented from becoming brittle during water jet laser processing, and therefore the breakage of the resin film during subsequent expansion can be suppressed. Furthermore, the elongation of the resin film at break is a predetermined value or more, so that the expandability of the resin film is good.
[0117] Therefore, the adhesive tape for electronic component processing of this embodiment can be suitably used when dicing a substrate to be processed by water jet laser processing.
[0118] Hereinafter, each component of the adhesive tape for processing electronic parts according to this embodiment will be described.
[0119] 1. Resin film The resin film in this embodiment is a member that supports the adhesive layer.
[0120] (1) Characteristics of resin film (a) Storage modulus In this embodiment, the storage modulus of the resin film at 100° C. is 1×10 7 Pa or more than 5×10 7 Pa or more, and 8 Pa or more. As described in the first embodiment, in the water jet laser processing, heat is generated instantaneously when the substrate to be processed is diced, and the heat is also transmitted to the adhesive tape for electronic component processing. In this state, the adhesive tape for electronic component processing is subjected to the water jet. Therefore, if the adhesive tape for electronic component processing becomes soft due to heat, it is considered that the adhesive tape for electronic component processing is easily damaged by the water pressure of the water jet. On the other hand, if the adhesive tape for electronic component processing is relatively hard even when heated, it is considered that damage to the adhesive tape for electronic component processing caused by the water pressure of the water jet can be reduced. Here, the storage modulus can be used as an index of hardness. Therefore, by having the storage modulus of the resin film at high temperatures in the above range, breakage of the resin film during water jet laser processing can be suppressed. The upper limit of the storage modulus of the resin film at 100 ° C. is not particularly limited as long as it satisfies the storage modulus of the resin film at 25 ° C. described later.
[0121] The storage modulus of the resin film at 25° C. is, for example, 1×10 9 Pa or less, 5×10 8Pa or less, and 1×10 8 The storage modulus of the resin film at room temperature may be not more than 1 Pa. When the storage modulus of the resin film at room temperature is within the above range, the expandability of the resin film is good.
[0122] The storage modulus is measured by the following method. First, the adhesive layer is removed from the adhesive tape for electronic component processing, and the resin film is taken out. In addition, when a primer layer is disposed on the adhesive layer side of the resin film, the primer layer is also removed. The adhesive layer removal method and the primer layer removal method are as described in the first embodiment. Next, the resin film is cut into a size of 8 mm in width and 50 mm in length. Next, dynamic viscoelasticity measurement (DMA) is performed under the following conditions to measure the storage modulus at 25°C and 100°C. For example, a dynamic viscoelasticity measurement device (DMA) "RSA-3" manufactured by TA Instruments Japan is used as the dynamic viscoelasticity measurement device. When it is known that the resin film constituting the adhesive tape for electronic component processing is a commercially available resin film, the commercially available resin film may be used to measure the storage modulus.
[0123] <Measurement conditions> Test piece: rectangular test piece (width 5mm, length 60mm) Measurement mode: Tensile Chuck distance: 10mm Temperature range: 0℃ to 250℃ Heating rate: 10mm / min Frequency: 1Hz Distortion: 0.1%
[0124] Methods for controlling the storage modulus of the resin film at 100° C. include, for example, a method of adjusting the material of the resin film and a method of adjusting the heat resistance of the resin film.
[0125] When adjusting the material of the resin film, for example, polypropylene, polyester elastomer, or engineering plastic is used, the heat resistance of the resin film tends to be high and the storage modulus at high temperatures tends to be large, whereas, for example, polyethylene or polyvinyl chloride is used, the heat resistance of the resin film tends to be low and the storage modulus at high temperatures tends to be small.
[0126] When the heat resistance of a resin film is high, the storage modulus at high temperatures tends to be large, whereas when the heat resistance of a resin film is low, the storage modulus at high temperatures tends to be small.
[0127] (b) Laser light non-absorption The resin film in this embodiment is non-absorbent to laser light. "Non-absorbent to laser light" means that the resin film is transparent to the wavelength of the laser light used in water jet laser processing, or is reflective to the wavelength of the laser light used in water jet laser processing. Specifically, when the transmittance of the laser light of the resin film is T (%), the transmittance of the resin film in the range of the wavelength λ±20 nm of the laser light is preferably within T±2.0%. In the transmission spectrum of the resin film, if the transmittance in a predetermined wavelength range satisfies the above relationship, the resin film can be said to be non-absorbent to laser light, that is, to have no absorption band at the wavelength of the laser light.
[0128] In particular, the resin film is preferably transparent to the wavelength of the laser light used in the water jet laser processing. The transmittance T of the laser light through the resin film is, for example, 50% or more, or may be 70% or more, or may be 90% or more.
[0129] As a method for controlling the laser light absorptivity and non-absorption of the resin film, for example, a method for adjusting the material of the resin film can be mentioned.
[0130] In addition, the resin film may be colorless or colored as long as it is non-absorbent of the laser light. For example, when the wavelength of the laser light is 532 nm, the resin film may be yellowish.
[0131] (c) Elongation at break In this embodiment, the elongation at break of the resin film is 500% or more, may be 1000% or more, or may be 2000% or more. If the initial elongation at break is within the above range, the expandability of the resin film is good. In addition, if the initial elongation at break is within the above range, the breakage of the resin film during water jet laser processing and expansion can be suppressed. On the other hand, the upper limit of the initial elongation at break is not particularly limited.
[0132] The elongation at break of the resin film is measured in accordance with JIS K7127:1999 under the following conditions. The tensile tester used is, for example, "Tensilon RTF1150" manufactured by A&D Co., Ltd.
[0133] <Measurement conditions> Test piece: rectangular test piece (width 10mm, length 60mm) ·Distance between gauge lines: 25mm Initial distance between chucks: 25mm Pulling speed: 200mm / min ·Temperature: 23±2℃ ·Humidity: 50±10%RH
[0134] When measuring the elongation at break of the resin film, the adhesive layer is removed from the adhesive tape for electronic component processing, and the resin film is taken out. In addition, when a primer layer is disposed on the adhesive layer side of the resin film, the primer layer is also removed. The method for removing the adhesive layer and the method for removing the primer layer are as described in the first embodiment above.
[0135] Examples of methods for controlling the elongation at break of a resin film include adjusting the material of the resin film, adjusting the tensile modulus of elasticity of the resin film, and adjusting the manufacturing method of the resin film.
[0136] When adjusting the material of the resin film, for example, polyolefin, polyvinyl chloride, or thermoplastic elastomer is used, the initial elongation at break tends to be large, whereas, for example, polyethylene terephthalate, polyamide, or polyether ether ketone is used, the initial elongation at break tends to be small.
[0137] If the tensile modulus of the resin film is small, the resin film tends to be soft and therefore tends to have a large initial elongation at break, whereas if the tensile modulus of the resin film is large, the resin film tends to be hard and therefore tends to have a small initial elongation at break.
[0138] When adjusting the production method of the resin film, if the resin film is a non-stretched film, the initial elongation at break tends to be large, whereas if the resin film is a stretched film, the initial elongation at break tends to be small.
[0139] (d) Thickness In this embodiment, the thickness of the resin film is 100 μm or more, and may be 150 μm or more. By the thickness of the resin film being within the above range, the elongation at break after the water jet laser processing can be easily adjusted to be within a predetermined range. On the other hand, the thickness of the resin film is, for example, 1000 μm or less, may be 500 μm or less, or may be 300 μm or less. If the thickness of the resin film is within the above range, the expandability of the resin film is good. Specifically, the thickness of the resin film is 100 μm or more and 1000 μm or less, may be 100 μm or more and 500 μm or less, may be 150 μm or more and 500 μm or less, or may be 150 μm or more and 300 μm or less.
[0140] (2) Resin film material The material of the resin film is not particularly limited as long as it satisfies the above-mentioned properties of the resin film, and is the same as the material of the resin film in the first embodiment.
[0141] 2. Adhesive layer The adhesive layer in this embodiment is the same as the adhesive layer in the first embodiment.
[0142] 3. Other configurations The adhesive tape for processing electronic parts of this embodiment may have other components, if necessary, in addition to the above-mentioned resin film and adhesive layer.
[0143] The adhesive tape for processing electronic parts of this embodiment may have a separator on the surface of the adhesive layer opposite to the resin film.
[0144] 4. Characteristics of adhesive tapes for electronic component processing The properties of the adhesive tape for processing electronic parts of this embodiment are similar to the properties of the adhesive tape for processing electronic parts of the above-mentioned first embodiment.
[0145] 5.Applications The applications of the adhesive tape for processing electronic parts of this embodiment are similar to those of the adhesive tape for processing electronic parts of the first embodiment.
[0146] B. Manufacturing methods for electronic components The method for manufacturing electronic components in the present disclosure includes an application step of applying the above-mentioned adhesive tape for electronic component processing to a first surface of a workpiece substrate, a dicing step of cutting the workpiece substrate into a plurality of chips with a laser guided by a water jet, an expanding step of stretching the adhesive tape for electronic component processing to increase the spacing between the chips, and a pick-up step of picking up the chips from the adhesive tape for electronic component processing.
[0147] 3(a) to (f) are process diagrams illustrating the method for manufacturing electronic components according to the present disclosure, and are examples in which the adhesive layer is an energy ray curable adhesive layer. First, as shown in FIG. 3(a), a bonding process is performed in which one side of the adhesive tape 10 for electronic component processing is bonded to a ring frame 31, and a substrate 11 to be processed is bonded to one side of the adhesive tape 10 for electronic component processing. Next, as shown in FIG. 3(b), a dicing process is performed in which the substrate 11 is cut into chips 12. Next, as shown in FIG. 3(c), an expanding process is performed in which the adhesive tape 10 for electronic component processing is stretched to widen the gap between the chips 12. Next, as shown in FIG. 3(d), a curing process is performed in which the adhesive layer of the adhesive tape 10 for electronic component processing is irradiated with energy rays 32 from the resin film side to be cured, thereby reducing the adhesive strength. Next, as shown in FIG. 3(e), a picking process is performed in which the chips 12 are picked up from the adhesive tape 10 for electronic component processing. Next, as shown in FIG. 3(f), a mounting (die bonding) step is performed in which the picked up chip 12 is attached to a substrate 30.
[0148] In the present disclosure, since the above-mentioned adhesive tape for electronic component processing is used, the expandability of the resin film of the adhesive tape for electronic component processing is good, and breakage of the resin film of the adhesive tape for electronic component processing during the dicing process and the expanding process can be suppressed.
[0149] When the adhesive layer is an energy ray curable adhesive layer, a curing step is performed after the dicing step and before the picking step, in which the adhesive layer of the adhesive tape for processing electronic components is irradiated with energy rays to be cured. The curing step may be performed between the dicing step and the expanding step, or between the expanding step and the picking step.
[0150] General methods and conditions can be applied to each step in the method for producing electronic components according to the present disclosure.
[0151] The present disclosure is not limited to the above-described embodiments. The above-described embodiments are merely examples, and anything that has substantially the same configuration as the technical idea described in the claims of the present disclosure and exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0152] The present disclosure will be further described below with reference to examples and comparative examples.
[0153] [Example 1] An adhesive composition was prepared by diluting 100 parts by mass of adhesive base agent (acrylic acid copolymer), 50 parts by mass of urethane acrylate (ultraviolet-curable compound, 9 functional groups, molecular weight 4100, active content 65%), 1.5 parts by mass of photopolymerization initiator (IGM Resins BV "Omnirad 819"), and 3 parts by mass of crosslinking agent (isocyanate-based curing agent (tolylene diisocyanate (TDI)-based adduct type (trimethylolpropane adduct)), solid content 75%) with a mixed solvent of toluene and methyl ethyl ketone (mass ratio 1:1) and thoroughly dispersing the mixture.
[0154] The above adhesive composition was applied onto a polyethylene terephthalate (PET) separator ("PET50x1-M-J2" manufactured by Nippa Corporation, thickness 50 μm) so that the thickness after drying would be 50 μm, and the composition was dried in an oven at 110°C for 3 minutes to form an adhesive layer.
[0155] A 150 μm thick polypropylene film ("PL815T" manufactured by Diaplus Film Co., Ltd.) was laminated onto the adhesive layer, and then aging was carried out at 40° C. for 3 days to prepare an adhesive tape for processing electronic components.
[0156] [Example 2] An adhesive tape for processing electronic parts was produced in the same manner as in Example 1, except that a polyester elastomer film having a thickness of 170 μm ("G847" manufactured by Kurabo Industries, Ltd.) was used.
[0157] [Comparative Example 1] An adhesive tape for processing electronic parts was produced in the same manner as in Example 1, except that a polyvinyl chloride film having a thickness of 200 μm ("New Celeb 200T" manufactured by Okamoto Corporation) was used.
[0158] [Comparative Example 2] An adhesive tape for processing electronic parts was produced in the same manner as in Example 1, except that a polypropylene film having a thickness of 80 μm (manufactured by Diaplus Film Co., Ltd., "LS1073-11") was used.
[0159] [Comparative Example 3] An adhesive tape for processing electronic parts was produced in the same manner as in Example 1, except that a polyethylene film having a thickness of 200 μm ("Emasoft Nashiji 200" manufactured by Okamoto Corporation) was used.
[0160] [Comparative Example 4] An adhesive tape for processing electronic parts was produced in the same manner as in Example 1, except that a polyethylene terephthalate film having a thickness of 188 μm ("Cosmoshine A4160" manufactured by Toyobo Co., Ltd.) was used.
[0161] [Comparative Example 5] An adhesive tape for processing electronic parts was produced in the same manner as in Example 1, except that a pink polyethylene film having a thickness of 200 μm ("Ema Soft Color P" manufactured by Okamoto Corporation) was used.
[0162] [Comparative Example 6] An adhesive tape for processing electronic parts was produced in the same manner as in Example 1, except that a blue polyethylene film having a thickness of 200 μm ("Ema Soft Color B" manufactured by Okamoto Corporation) was used.
[0163] [Comparative Example 7] An adhesive tape for processing electronic parts was produced in the same manner as in Example 1, except that a polyamide film having a thickness of 25 μm ("Uniamide" manufactured by Unitika Ltd.) was used.
[0164] [Comparative Example 8] An adhesive tape for processing electronic parts was produced in the same manner as in Example 1, except that a polyether ether ketone film having a thickness of 50 μm ("EXPEEK" manufactured by Kurabo Industries, Ltd.) was used.
[0165] [evaluation] (1) Thickness of resin film The thickness of the resin film was measured using a digital thickness gauge.
[0166] (2) Transmission spectrum of resin film The transmission spectrum of the resin film was measured using a Shimadzu Corporation ultraviolet-visible spectrophotometer "UV-2700" to determine the transmittance at a wavelength of 532 nm and the transmittance in a specified wavelength range.
[0167] (3) Storage modulus of resin film The adhesive tape for electronic component processing was cut to a size of 5 mm wide and 60 m long to obtain a test piece. Next, dynamic viscoelasticity measurement was performed under the following conditions using a dynamic viscoelasticity measuring device (DMA) "RSA-3" manufactured by TA Instruments Japan, and the storage modulus at 100°C was measured.
[0168] <Measurement conditions> Test piece: rectangular test piece (width 5mm, length 60mm) Measurement mode: Tensile Chuck distance: 10mm Temperature range: 0℃ to 250℃ Heating rate: 10mm / min Frequency: 1Hz Distortion: 0.1%
[0169] (4) Elongation of resin film at break (4-1) Initial elongation at break The resin film was cut into a size of 10 mm x 60 mm to obtain a test piece. A tensile test was performed using an A&D "Tensilon RTF1150" tensile tester under the following conditions in accordance with JIS K7127:1999 to determine the elongation at break.
[0170] <Measurement conditions> Test piece: rectangular test piece (width 10mm, length 60mm) ·Distance between gauge lines: 25mm Initial distance between chucks: 25mm Pulling speed: 200mm / min ·Temperature: 23±2℃ ·Humidity: 50±10%RH
[0171] (4-2) Elongation at break of adhesive tape for electronic component processing after water jet laser processing As shown in FIG. 2, the adhesive tape 10 for electronic component processing was cut into a size of 30 mm×60 mm. Next, the adhesive tape 10 for electronic component processing was placed on a glass plate 51 so that the resin film faced the glass plate side and the adhesive layer faced outward, and was fixed with Kapton tape 52 to obtain a laminate for processing 50. Using a water jet laser processing dicing device ("Laser Microjet" manufactured by SYNOVA), 10 passes (5 round trips) were made on the same location of the laminate for processing 50 from the adhesive layer side as shown by the arrow in FIG. 2 under the following conditions. Next, as shown by the dashed line in FIG. 2, the adhesive tape 10 for electronic component processing was cut into a width of 10 mm at the center using a cutter to obtain a test piece 53.
[0172] <Water jet laser processing conditions> Laser wavelength: 532nm Cutting speed: 100mm / s Laser beam diameter (water jet diameter): 50μm Water pressure: 25MPa Average Power: 6.6W Frequency: 700Hz Pulse width: 180μsec
[0173] Next, a tensile test was performed under the above conditions using an A&D "Tensilon RTF1150" tensile tester in accordance with JIS K7127:1999 to determine the elongation at break. In Table 1, "break" refers to the adhesive tape for electronic component processing breaking during water jet laser processing or during processing prior to elongation measurement due to significant damage caused by water jet laser processing.
[0174] [Table 1]
[0175] In Examples 1 and 2, the thickness of the resin film was a predetermined value or more, the storage modulus of the resin film at 100°C was a predetermined value or more, the resin film was non-absorbent to laser light, and the elongation at break of the resin film was a predetermined value or more, so that the elongation at break of the adhesive tape for electronic component processing after water jet laser processing was a predetermined value or more.
[0176] On the other hand, in Comparative Examples 1 and 3, the resin film had a small storage modulus at 100°C, so the elongation at break of the adhesive tape for electronic component processing after water jet laser processing was small. In Comparative Example 2, the resin film was thin, so the elongation at break of the adhesive tape for electronic component processing after water jet laser processing was small. In Comparative Example 4, the elongation at break of the adhesive tape for electronic component processing after water jet laser processing was small. In Comparative Examples 5 and 6, the resin film absorbed the laser light, so it broke during laser irradiation. In Comparative Examples 7 and 8, the resin film was thin, the storage modulus at 100°C of the resin film was small, and the elongation at break of the resin film was small, so it broke during preparation of the test piece for the tensile test after laser irradiation. [Explanation of symbols]
[0177] 1 ... Resin film 2 … Adhesive layer 10...Adhesive tape for electronic component processing
Claims
1. An adhesive tape for processing electronic components, comprising: a resin film; and an adhesive layer disposed on a first surface of the resin film, The pressure-sensitive adhesive tape for electronic component processing, wherein the elongation at break of the pressure-sensitive adhesive tape for electronic component processing after water jet laser processing is 50% or more.
2. An adhesive tape for processing electronic components, comprising: a resin film; and an adhesive layer disposed on a first surface of the resin film, The thickness of the resin film is 100 μm or more, The storage modulus of the resin film at 100° C. is 1×10 7 Pa or more, the resin film is non-absorbent to laser light, The adhesive tape for processing electronic components, wherein the resin film has an elongation at break of 500% or more.
3. 3. The pressure-sensitive adhesive tape for processing electronic parts according to claim 1, wherein the resin film contains polypropylene or a polyester elastomer.
4. a bonding step of bonding the adhesive tape for processing electronic components according to any one of claims 1 to 3 to a first surface of a substrate to be processed; a dicing step of cutting the substrate into chips by a laser guided by a water jet; an expanding step of stretching the adhesive tape for electronic component processing to increase the distance between the chips; a pick-up step of picking up the chip from the adhesive tape for electronic component processing; The method for manufacturing an electronic component includes the steps of:
Citation Information
Patent Citations
JP1973086937A
JP1975000370A
Adhesive tape for fixing semiconductor wafer
JP2005167042A
water permeable adhesive tape
JP3824874B2
Adhesive tape for laser dicing
JP4087144B2